PENERAPAN TIPE COOPERATIVE SCRIPT UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS V SEKOLAH DASAR - Sari, Evi Novita; Halidjah, Siti; Sugiono, Sugiono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThis study aims to de scribe the application of cooperative Script type that can improve the speaking skill in class V A public elementary school 43 river Kakap re gency cemetery. This form of researsh is a classroom action researsh with the subjeck of researsh teachers and students of class V A that amounted to 30 people. The method used is desciptive Â method. Data collection techniques used are obsevation and careful document. Data analy sis techniques used are calculate the average and percent age. This researsh is done 3 cycles and each cycle consists of 2 meetings with the results obtained are 1) The ability of techers to design learning from cycle 1 is 3,29, cycle 2 is 3,59, and cycle 3 is 3,84; 2) The ability of teachers to implement learning starting from cycle 1 is 3,75, cycle 2 is 3,73 and cycle 3 is 3,86; 3) Student speaking skill starts cycle 1 equal to 52,77, cycle 2 equal to 70,27, and cycle 3 equal to 85,66. From the date obtainet showed that by using cooperative script method can improve the speaking skills of students in the elementary school of state elementary Scool 43 River Kakap District Kuburaya.Â Keywords : Implementation, Speech Skills, Cooperative Script Type.